2015
DOI: 10.14334/jitv.v20i4.1247
|View full text |Cite
|
Sign up to set email alerts
|

Endemicity of avian influenza in ducks living around commercial layer farms

Abstract: Tetua dari semua virus avian influenza adalah itik atau unggas air lainya yang kemudian mengalami mutasi dan adaptasi sehingga menjadi patogen pada ayam atau unggas lainya. Oleh karena itu, penyidikan keberadaan virus influenza pada itik terutama yang dekat dengan peternakan ayam sangat penting. Serum dari 54 ekor itik dan 51 entok yang dipelihara penduduk disekitar peternakan ayam ras petelur komersial di Kabupaten Cianjur dan Sukabumi diambil pada bulan Maret dan April 2014. Indikasi adanya infeksi dilakukan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Based on the duck sera’s susceptibility to recombinant hemagglutinins and neuraminidases in indirect enzyme-linked immunosorbent assay and dot blot studies, the H9N2 subtype was believed to exist in Java, Indonesia, duck population [ 11 ]. This is the first report of H9N2 outbreaks in Java, and surveillance will be required to confirm the existence of H9N2 subtypes via virus isolation and molecular characterization.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the duck sera’s susceptibility to recombinant hemagglutinins and neuraminidases in indirect enzyme-linked immunosorbent assay and dot blot studies, the H9N2 subtype was believed to exist in Java, Indonesia, duck population [ 11 ]. This is the first report of H9N2 outbreaks in Java, and surveillance will be required to confirm the existence of H9N2 subtypes via virus isolation and molecular characterization.…”
Section: Introductionmentioning
confidence: 99%
“…(Peiris et al 2007) The circulation of the H9N2 subtype in Indonesia was also initially found in 2015, and according to Genbank data, more than 40 virus isolates were isolated from various places in this country. (Tarigan et al 2015;Jonas et al 2018) Infection of the H9N2 subtype in humans has never been reported in Indonesia, but molecular analysis of isolated isolates showed the presence of the amino acid Leucine (L) at residue 216 of the receptor binding site of the hemagglutinin (HA) gene. ( Previous study related to the use of sialidase as an antiviral has been carried out and illustrated in silico, in vitro to in ovo with satisfactory results.…”
Section: Introductionmentioning
confidence: 99%